2003
DOI: 10.1046/j.1432-1033.2003.03604.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the kinetics and order of tyrosine phosphorylation in the T‐cell receptor ζ chain by the protein tyrosine kinase Lck

Abstract: We report experiments to investigate the role of the physiologically relevant protein tyrosine kinase Lck in the ordered phosphorylation of the T-cell receptor f chain. Six synthetic peptides were designed based on the sequences of the immunoreceptor tyrosine-based activation motifs (ITAMs) of the f chain. Preliminary 1 H-NMR studies of recombinant f chain suggested that it is essentially unstructured and therefore that peptide mimics would serve as useful models for investigating individual ITAM tyrosines. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…3a,b ), yielding k cat , K M and the Hill coefficients ( n H ) ( Table 1 ). The observed k cat values varied from 1-7 s −1 , in the same range as solution measurements on recombinant WT Lck using a peptide substrate corresponding to the autophosphorylation site of c-Src 26 , but orders of magnitude higher than a recent study using peptide substrates corresponding to individual tyrosines in CD3ζ 27 . The apparent 2-D K M values (200-500 μm −2 ) are similar to physiological densities of CD3ζ (100-360 μm −2 ), suggesting that Lck is operating in T cells at almost its maximal capacity while maintaining sensitivity to changes in the substrate concentration.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…3a,b ), yielding k cat , K M and the Hill coefficients ( n H ) ( Table 1 ). The observed k cat values varied from 1-7 s −1 , in the same range as solution measurements on recombinant WT Lck using a peptide substrate corresponding to the autophosphorylation site of c-Src 26 , but orders of magnitude higher than a recent study using peptide substrates corresponding to individual tyrosines in CD3ζ 27 . The apparent 2-D K M values (200-500 μm −2 ) are similar to physiological densities of CD3ζ (100-360 μm −2 ), suggesting that Lck is operating in T cells at almost its maximal capacity while maintaining sensitivity to changes in the substrate concentration.…”
Section: Resultsmentioning
confidence: 51%
“…Our data reported here have revealed that cooperativity is at least partially encoded in the TCR proximal signaling architecture itself. A recent mathematical model by Mukhopadyay et al 12 suggested that the TCR proximal signaling ultrasensitivity arises from the multiple phosphoacceptor sites on CD3ζ, sequential phosphorylation of these sites by Lck 27 , and protection from dephosphorylation by ZAP-70. We have obtained experimental support for ZAP-70 protection against CD45 dephosphorylation ( Fig 4a,c ) but found that the ability of ZAP-70 to bind phospho-ITAMs did not alter the cooperativity of the kinase-phosphatase reaction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This preference explains why Lck does not readily phosphorylate tyrosine residues in LAT and SLP-76 that contain an aspartate residue at the −1 position (Figure 3). It also explains why Lck phosphorylates the first tyrosine residue in each ITAM faster than the second one (Housden et al, 2003), as the first tyrosine is typically preceded by a leucine while the second is preceded by a smaller aliphatic or polar residue (Figure 3A). …”
Section: Resultsmentioning
confidence: 99%
“…5, “ITAMs”). Several studies showed that Lck initially phosphorylates the N-terminal tyrosine of ITAMs and then later phosphorylates the C-terminal tyrosine (61, 69); however, the precise order of ITAM phosphorylation is still under investigation (60, 61, 63, 69). In the computational part of our study that focused on Lck, we found three possible scenarios for ordered ITAM phosphorylation that were consistent with the SILAC data (Fig.…”
Section: Discussionmentioning
confidence: 99%